PhD Thesis Summaries 2025 (New Zealand Sociology, 2025)
PhD Thesis Summaries 2025. This section showcases recently completed PhD theses in sociology and associated disciplines in Aotearoa New Zealand.Oliver Jules Birch, Joshua James, Roshana Kamran Ali, Kalym Lipsey, Brittany Palatchie, Dani Pickering, Emmy Rākete, Swakshadip Sarkar & Hafsa Tameez